Addressing knowledge gaps on emerging issues in weather and climate extreme events: a systematic review - Muhammad Kafi, Kamil; Ponrahono, Zakiah; Salisu Barau, Aliyu (Springer Science and Business Media B.V., 2024)
This paper examines various studies on weather and climate extreme events (WCEE) to identify thematic trends and research gaps and suggest directions for further studies. The review identifies 14 subthemes and 23 research focuses, that address impacts and issues in the pre-, during-, and post-disaster phases. Using a matrix of WCEE dimensionality and content matrix analysis, we analyze the distribution and research focus of these studies, revealing areas with both extensive and limited research. While significant literature exists on certain WCEE subthemes, with a strong focus on damage assessment, spatial extent, losses, and disaster management approaches, only a limited number of studies have explored crucial areas such as risk prediction, urban planning, water quality, urban resilience, and public health dimensions. These areas are vital for effective disaster risk reduction. To bridge the knowledge gaps in these areas and other areas with multi-dimensional outlooks within the context of WCEE, we recommend prioritizing research in these subthemes. Our findings underscore the importance of interdisciplinary collaboration and the need for additional research to enhance our understanding of WCEE. Through evidencebased strategies, policymakers and practitioners can develop measures to enhance resilience and mitigate the impacts of WCEE.